Meningococcal carriage in young adults six years after meningococcal C conjugate (MCC) vaccine catch-up campaign in Salvador, Brazil. Issue 14 (23rd March 2020) - Ferreira, Viviane Matos; Ferreira, Ítalo Eustáquio; Chang, How-Yi; Nunes, Amélia Maria Pithon Borges; Topaz, Nadav; Pimentel, Ellen Reis; Moura, Ana Rafaela Silva Simões; Ribeiro, Guilherme Sousa; Feitosa, Caroline Alves; Reis, Mitermayer Galvão; Wang, Xin; Campos, Leila Carvalho
Highlights: Mostly non-groupable strains. Low prevalence of serogroup C. High genetic diversity among carried strains. Abstract: Meningococcal carriage studies are important to improve the knowledge of disease epidemiology as well as to support appropriate vaccination strategies. We conducted a cross-sectional study to determine the prevalence and genotypic characteristics of meningococci collected from young adults in Salvador, Brazil six years after a meningococcal C conjugate vaccine catch-up campaign. From August through November 2016, oropharyngeal swabs were collected from 407 students aged 1824 years attending a private college in Salvador, Brazil. Neisseria meningitidis was identified by standard microbiology methods and real time PCR. Genetic characteristics of meningococci were assessed by rt-PCR and/or whole genome sequencing. We also investigated potential factors associated with carriage. N. meningitidis was detectable in 50 students, 39 by both culture and rt-PCR, 7 by culture alone and 4 by rt-PCR alone, resulting in an overall meningococcal carriage prevalence of 12.3% (50/407). Carriage was independently associated with male sex (adjusted PR: 1.97; 95% CI: 1.12–3.46; p = 0.018) and attending bars or parties at least once per month (aPR: 3.31; 95% CI: 1.49–7.38; p = 0.003). Molecular tests identified 92% (46/50) N. meningitidis as non-groupable, of which 63% (29/46) had the capsule null genotype; 14 NG isolates contained disrupted capsule backbones and belonged to the following genogroups: 7 B, 3 Z, 3 E and 1 W. One isolate belonged to genogroup C tested only by PCR; 3 isolates contained a complete B capsule backbones, 2 of which were determined to be NG by slide agglutination serogrouping. While most meningococcal carriage isolates were non-groupable, there was a high degree of genetic diversity present in the collection, as evidenced by 25 unique STs being detected. The carriage prevalence of meningococcal serogroup C was low among young adults. Continuous vaccination is important to maintain reduced meningococcal carriage and transmission, inducing herd protection.